New species of Euglossa II. (Hymenoptera: Apidae) - Dressler, Robert L. (1982)
Keys are provided for males of the analis, cybelia and piliventris species groups, and new species ofsubspecies are described in each. In addition, a new species allied to E. stellfeldi and a new species of subgenus Euglossella are described.